Effects of Dietary Yucca Schidigera Extract and Oral Candida utilis on Growth Performance and Intestinal Health of Weaned Piglets - Yang, Zhenguo; Wang, Yao; He, Tianle; Ziema Bumbie, Gifty; Wu, Liuting; Sun, Zhihong; Sun, Weizhong; Tang, Zhiru (Frontiers in Nutrition, 2021)
Weaning piglets experienced the transformation from breast milk to solid feed and present the proliferation of pathogens, the presence of diarrhea, poor growth performance and even death. Plant extracts and probiotics have certain potential in improving animal growth performance, antioxidant capacity and immune function. The purpose of this study was to explore the effects of dietary yucca schidigera extract (YSE) and oral Candida utilis (CU) on growth performance and intestinal health weaned piglets. According to a 2 × 2 factorial design with the main factors being CU (orally administered 1 mL of 0.85% saline with or without CU; fed basal diet with or without 120 mg/kg YSE), forty 28 d healthy weaned piglets were randomly allocated into four groups of 10 barrows each: (1) piglets fed basal diet and orally administered 1 mL of 0.85% saline (CON); (2) piglets fed basal diet and orally administered 1 mL 1 × 109 cfu/mL C. utilis in 0.85% saline (CU); (3) piglets fed the basal diet containing YSE (120 mg/kg) and orally administered 1 mL of 0.85% saline (YSE); (4) Piglets fed the basal diet containing 120 mg/kg YSE and 1 mL 1 × 109 cfu/mL C. utilis in 0.85% saline (YSE+CU). This study lasted 28 days and evaluated the effects of dietary YSE and oral CU on growth performance, immunity, antioxidant function, ileal morphology, and intestinal microflora in weaned piglets. Dietary YSE increased ADG, the spleen and lymph node indexes, serum GLU, BUN, T-SOD, T-AOC, CAT concentrations, ileal villus height and villus height/crypt depth, jejunal occludin, and β-definsin-2 concentrations and ileal occludin concentration in weaned piglets (P < 0.05); decreased the diarrhea rate and mortality, rectal pH and urine pH, the BUN and MDA concentrations, crypt depth (P < 0.05); improved the diversity of cecal microflora. Orally CU increased ADG, and ADFI, the T-SOD, T-AOC, and CAT activity, ileal villus height, villus height/crypt depth, jejunum occludin, and β-definsin-2 concentrations (P < 0.05); reduced the diarrhea rate and mortality, urine pH, the BUN and MDA concentrations, crypt depth (P < 0.05); improved the diversity of cecal microflora. Dietary YSE and orally CU increased the T-SOD, T-AOC, and CAT activity, villus height/crypt depth, jejunal occludin concentration; reduced the diarrhea rate of weaned piglets by 28%, gastric pH, ileal pH, cecal pH and urine pH, MDA, crypt depth; improved the diversity of cecal microflora. YSE and CU could improve the growth performance, reduce the diarrhea rate, improve intestinal health, and increase the diversity and abundance of cecal microflora in weaned piglets and expected to be used as antibiotics alternative feed additives in the production of weaned piglets.